The Importance of Proximity, Target Congruence, and Guardianship of Korean Youth Victims: Applying Latent Class Analysis to Identify Subtypes of Poly-Victimization - Cho, Sujung (Crime & delinquency, 2024)
Poly-victimization, or exposure to multiple types of victimization, is particularly common among children and adolescents. This study uses Lifestyle-Routine Activity Theory and Target Congruence Theory to examine distinct subgroups of Korean youth who have experienced poly-victimization through the estimation of a latent class analysis. This study uses a nationally representative sample?the 2018 National Survey on the Rights of Children and Youth (N?=?9,060, Grades 4?12). Results found four distinct subgroups of Korean youth who have experienced violent victimization: low risk/non-victims (54.1%), poly-victims (4.1%), verbal bullying victims (10.5%), and victims of parental abuse (31.3%). Distal outcomes such as suicidality and dropout were also examined regarding victimization experiences. Policy implications such as detecting victimization and early intervention/prevention programs are also discussed.